ALGORITHM FOR DIAGNOSIS AND THERAPY OF DIFFERENTIATED THYROID CANCER WITH INTEGRATION OF MOLECULAR-GENETIC PROFILING (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The objective of this study was to evaluate the prevalence and clinicopathological relevance of BRAF-V600E, RET/PTC, TERT, RAS